PELATIHAN PEMANFAATAN SISIK IKAN MENJADI PRODUK BERNILAI EKONOMI TINGGI DI JEMAAT GPM LANUD PATTIMURA KOTA AMBON - Ruban, Angela; Pattimukay, Kesya (Universitas Pattimura, 2023)
Fishery products such as fish are generally sold in fresh or processed conditions, while fish scales have been discarded. The Community Service activities carried out aim to provide information to the GPM Lanud Pattimura congregation about the utilization of fish scales into products of high economic value using lecture and discussion methods and training in making accessories such as earrings, brooches and decorative flowers. The results obtained showed that there was an increase in knowledge about and skills in making products made from fish scales before and after the community participated in the activity. The conclusion of this activity illustrates that the presentation of material in the form of lectures and discussions has increased community knowledge, and the training conducted can improve community skills as an entrepreneurial opportunity to increase family income